Association between Foeto-maternal Bleeding and Hypertension in Pregnancy. Issue 5673 (27th September 1969) - Jones, Peter; McNay, Angus; Walker, William
Abstract : A blind prospective survey of foeto-maternal bleeding in 200 primiparous pregnancies was carried out in an investigation of a possible association between foeto-maternal bleeding and hypertension in pregnancy. Evidence of foeto-maternal bleeding was found in 61% of 36 hypertensive pregnancies, and in 51% of 160 normotensive pregnancies, a difference which is not statistically significant. Significant differences between the hypertensive and the normotensive groups were found when foeto-maternal bleeding was related to gestation. In pregnancies that became hypertensive more foetal cells were found in the maternal circulation before week 36 than in normotensive pregnancies. In patients with oedema of the abdominal wall during pregnancy the incidence of foeto-maternal bleeding was significantly increased. These findings seem to explain why pre-eclamptic toxaemia is a significant predisposing factor in women who later develop Rh antibodies. It is recommended that anti-D gammaglobulin should be offered to all Rh-negative women with Rh-positive infants following a hypertensive pregnancy. Consideration should also be given to the question of administering anti-D gammaglobulin during Rh-negative hypertensive pregnancies if this procedure is proved to be both safe to mother and foetus and effective. The results provide contributory evidence that the placental vascular changes in toxaemic pregnancies precede the clinical signs and are not the result of hypertension.